Generalized solutions for singular double-phase elliptic equations under mixed boundary conditions - Liu, Jian; Zhao, Zengqin (Nonlinear Analysis: Modelling and Control, 2024)
In this article, we investigate at least one or two generalized solutions for double-phase singular elliptic equations with Hardy potential. We show the existence of at least one or two distinct generalized solutions under mixed boundary conditions via variational methods when the nonlinearity f satisfying suitable hypotheses.
Keywords: elliptic equations; double phase; Hardy potential; mixed boundary conditions